ChemInform Abstract: Heterocyclic Terpenes: Linear Furano‐ and Pyrroloterpenoids. Issue 30 (29th July 2014) - Wang, Bin; Wang, Lishu; Li, Yinglei; Liu, Yonghong
Abstract Review: literature published from January 2006 to December 2013; 180 refs.